Potential of Turmeric (Curcuma longa) as an Insect, Rodent Repellent and Its Antifungal and Allelopathic Effects on Lowland-based Rice Farming Systems: A Review - Johary Domaob; Aldrees Ansary Guro; Norhanie H. Jamel; Sittie Sahaya Samporna (Callus: Journal of Agrotechnology Science, 2026)
Rodents and insects in lowland rice farming areas destroy crops, which leads to severe food security problems. The widespread use of chemical rodenticides in society leads to environmental contamination, poses toxic risks to non-target organisms, and contributes to the development of resistance. This review evaluates the potential of turmeric (Curcuma longa L.) as a sustainable, plant-based alternative for insect, rodent repellent and its antifungal and allelopathic effects management. The researchers performed a systematic literature review that analyzed peer-reviewed studies from 1988 to 2025 and found 34 articles that met their research requirements. The findings demonstrate that turmeric contains bioactive compounds, which include curcuminoids and volatile oils such as ar-turmerone that show insecticidal and antifungal, and repellent effects. The compounds produce their effects through mechanisms that cause olfactory disruption and feeding deterrence. The existing evidence for rodent repellency remains scarce; yet turmeric shows strong potential to impact rodent behavior through its biological properties. The antifungal and allelopathic properties of the substance enable it to protect crops and enhance soil health. Turmeric shows promise as a sustainable pest control method because it functions as an environmentally friendly solution.